Determinants of Wholesale traders' participation in the purchasing consortium in Mbarara City, Uganda - Nabachwa, Sarah; Amwikirize, Annah; Twinamatsiko, Medard (Journal of Business and Management Review, 2024)
Wholesale businesses globally face operational challenges that necessitate adopting new mechanisms, especially in buying strategies. Purchasing consortiums, particularly among wholesale traders, are presented in existing literature as a promising avenue for traders to enhance the quality and value of their services. Consortium members can negotiate better prices and terms than they could by pooling resources and bargaining with suppliers. Unfortunately, the concept is not well-conceived and adopted among wholesale traders in developing countries, particularly Uganda. This study focused on establishing the determinants of wholesale traders' participation in the purchasing consortium in Mbarara City. A qualitative approach was used to examine the precursors, the barriers to participation, and the opportunities for wholesale traders to participate in purchasing consortiums. Data was collected from wholesale traders, city authorities and association leaders using the interview method. The study found that socio-demographic factors such as income, ethnicity and business longevity greatly determine the success of purchasing consortiums. To promote group buying and facilitate business growth in Mbarara City, it is recommended that Mbarara City Authorities create an enabling environment and support traders in organising themselves to participate in purchasing consortiums. This will reduce their business burden and promote business growth, hence development in Mbarara city.